+0  
 
0
264
1
avatar

lnX+ln(x+2)=3

Guest Apr 21, 2017
 #1
avatar+91135 
+3

Ln (x)  + Ln (x + 2)  = 3

 

And we can write

 

Ln  [ x ( x + 2) ]  = 3

 

This says that

 

e^3  = x ( x + 2)

e^3  = x^2 + 2x        rearrange

x^2 + 2x  - e^3  =  0

 

Using the quadratic formula, we have that  

 

x =  -1 -  √ [ 1 + e^3 ]     reject this  as it makes the logs undefned

or

x  =  -1 + √ [ 1 + e^3 ]    accept

 

 

cool cool cool

CPhill  Apr 21, 2017

5 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.